THE EFFECTIVENESS OF TNF-Α INHIBITOR THERAPY IN BLADDER PAIN SYNDROME/INTERSTITIAL CYSTITIS PATIENTS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Kholis, Ahmad; Soetojo; Djatisoesanto, Wahjoe (Indonesian Journal of Urology, 2021)
Objective: To evaluate the effectiveness of TNF-α inhibitor therapy in Bladder Pain Syndrome/Interstitial Cystitis (BPS/IC) patients compared to placebo, assessed using Global Response Assessment (GRA). Material & Methods: A systematic review and meta-analysis. Subjects were patients with moderate to severe diagnosis of BPS/IC who were given TNF-α inhibitor versus placebo, with the Global Response Assessment (GRA) (patient-reported self-reported BPS/IC treatment response scale). A systematic literature search was carried out on the English databases PubMed/MEDLINE and Science Direct, published until September 2020. Data were extracted independently and assessed the bias and quality of each selected article. Results: Initially there were 124 studies. After further selection, 2 RCT studies were included in the criteria for this study. The number of samples obtained was 85 patients. There is 1 study that used 400 mg of certolizumab pegol subcutaneously and 1 study used adalimumab 80 mg subcutaneously and followed by 40 mg subcutaneously for 2 weeks. Both studies had statistically low heterogeneity with I2 = 0% (P = 0.34), so fixed effect statistical model was used to determine the result. Furthermore, there was no significant difference (P = 0.32) between the number of GRA responders from the TNF-α inhibitor and placebo therapy groups, with odds ratio of 1.61 (CI = 0.65-4.00). Conclusion: TNF-α inhibitor therapy did not increase GRA responders when compared to placebo.